The art of the salon : the triumph of 19th-century painting - Wolf, Norbert, 1949- (Munich : Prestel, 2012)
The Paris Salons of the mid-nineteenth century are famous today above all for the paintings that were rejected more than for those that were actually shown. The rejected works form today's canon of art history and are regarded as heralds of a modern age. This book looks to reassess the other side of the art history of the nineteenth century. Salon Painting has often been dismissed as overly academic or staid. Now art historian Norbert Wolf turns back the pages of history as he reintroduces readers to the artistry and excellence of the Salon Painting in Europe, Britain, Russia and the US. In an opulent new book, illustrated throughout with gorgeous reproductions, Wolf looks at Salon painting from a variety of perspectives, such as the rise of the bourgeoisie and Paris's position as Europe's cultural capitol. Wolf examines masterpieces by Cabanel, Manet, Bierstadt, The Pre-Raphaelites, and Sargent, demonstrating how classical subjects gave way to modern concerns.
The revival of interest -- From the cultural economy of the nineteenth century -- On the boulevard of success -- Countries and artists -- Subjects -- The phenomenology of salon painting.
boek
Keywords: Painting -- 19th century -- History; Salons -- History -- 19th century